2012
DOI: 10.1177/1045389x12447986
|View full text |Cite
|
Sign up to set email alerts
|

Strain enhancement in lead-free Bi0.5(Na0.78K0.22)0.5TiO3 ceramics by CaZrO3 substitution

Abstract: The effects of CaZrO3 substitution on the crystal structure, electric field–induced strain, and piezoelectric properties of Bi0.5(Na0.78K0.22)0.5TiO3 ceramics have been investigated. The CaZrO3 substitution resulted in a transition from ferroelectric tetragonal to pseudocubic symmetry with relaxor characteristics, leading to degradations in the piezoelectric coupling coefficient, electromechanical quality factor, and piezoelectric coefficient d33. However, the electric field–induced strain was significantly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 44 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Addition of BF into BNKT20 has no significant influence on the phase structure of the ceramics, as evidenced by the almost unchanged (002)/(200) peak splitting at around 46° for all BF‐modified compositions. However, for BS‐, BM‐, and BA‐modified systems, the rhombohedral and tetragonal distortion gradually diminishes with the increasing BS, BM, and BA content, as the (002)/(200) splitting peaks of the coexisted phases finally merge into a single (200) peak at higher BS, BM, and BA content, suggesting that the crystal structure of the samples evolves from the rhombohedral–tetragonal coexisted phases to a pseudocubic symmetry …”
Section: Resultsmentioning
confidence: 99%
“…Addition of BF into BNKT20 has no significant influence on the phase structure of the ceramics, as evidenced by the almost unchanged (002)/(200) peak splitting at around 46° for all BF‐modified compositions. However, for BS‐, BM‐, and BA‐modified systems, the rhombohedral and tetragonal distortion gradually diminishes with the increasing BS, BM, and BA content, as the (002)/(200) splitting peaks of the coexisted phases finally merge into a single (200) peak at higher BS, BM, and BA content, suggesting that the crystal structure of the samples evolves from the rhombohedral–tetragonal coexisted phases to a pseudocubic symmetry …”
Section: Resultsmentioning
confidence: 99%
“…3 strain which was obtained in (BNT-BKT)-based materials have been found recently. [10][11][12][13][18][19][20][21][22][23] Generally, an enhancement of the strain in BNT-based materials is accompanied by the disruption of ferroelectric order, and corresponded to the depolarization temperature T d at nearly room temperature (RT). Therefore, to achieve an expected large strain, the introduced ABO 3 (end member perovskite) should be able to obviously disrupt the ferroelectric stability and result in a significant destabilization of the ferroelectric order.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the ceramics at x = 0.005, the pinched hysteresis loop was observed at temperatures ≥60 °C. Hong et al 33) also reported similar results in the (1 − x)BNKT-xCZ ceramics; from the results of the temperature dependence of dielectric loss and the changes in the shape of the P-E hysteresis loop, the presence of the relaxer phase above T F-R was suggested.…”
Section: Resultsmentioning
confidence: 55%
“…Therefore, it is considered that SZT addition into BNKT exists an influence on the ferroelectric-relaxor phase transition. Hong et al 33) reported that the pinched hysteresis loop in (1 − x)BNKT-xCaZrO 3 (CZ) is due to the ferroelectricrelaxor ferroelectric transition. The relationship between the pinched P-E hysteresis loop and the possibility of ferroelectric-relaxor ferroelectric transition was described by evaluating the temperature dependence of the P-E hysteresis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation